2011
DOI: 10.3109/10826084.2011.588878
|View full text |Cite
|
Sign up to set email alerts
|

Drugs on the Internet, Part II: Antidepressant Medication Web Sites

Abstract: Antidepressant medications have been the fastest growing category of use of pharmaceutical products over the past decade. Selected Internet web sites providing information on antidepressant medications were identified and assessed using code of conduct criteria for posting health information on the Internet as developed by the Health on the Internet Foundation. Thirteen representative web sites were evaluated. Degree of compliance with each of the eight criterion varied by site, though all 13 sites met the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…One such site that tries to maintain the integrity of information on websites is the HON Foundation. This nonprofit and nongovernmental website endorses the content of many webpages based on several criteria including: complementarity, justifiability, financial disclosure, and advertising policy (Health On the Net Foundation, 2011; Morgan and Montagne, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One such site that tries to maintain the integrity of information on websites is the HON Foundation. This nonprofit and nongovernmental website endorses the content of many webpages based on several criteria including: complementarity, justifiability, financial disclosure, and advertising policy (Health On the Net Foundation, 2011; Morgan and Montagne, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Wikipedia was always one of the top URLs on both Google and Yahoo SERPs despite which search term was used. A previous study on website quality regarding antidepressants also found that "regardless of search engine or search term the first page of results always yielded a link to Wikipedia.com" (Morgan and Montagne, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…The internet was found to be commonly used by people with depression for medicine fact seeking [ 52 ]. Antidepressant information is initiated and disseminated online more quickly than normal published literature while the accurate scientific facts about these medicines are limited in webpages as for emotive and promotional purposes [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been numerous evaluations of Web-based health information [ 6 , 10 ], fewer studies have evaluated Web-based medication information [ 3 , 9 , 15 - 22 ]. Given the importance of Web-based medication information to consumers [ 23 ], this study aimed to evaluate the medication information on 4 frequently used Australian websites.…”
Section: Introductionmentioning
confidence: 99%